1977
DOI: 10.1111/j.1365-2494.1977.tb01430.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of urea on the voluntary intake by calves of silages preserved with formaldehyde and formic acid

Abstract: Perennial ryegrass cv. S23 was preserved by fermentation (Q, or with the addition of 8 7 1 formalin (35% w/w formaldehyde) per t fresh herbage (F) or of 9-0 1 equal mixture (by vol.) of formalin and formic acid (85% w/w solution) per t fresh herbage (FF). These three silages comprised the treatments in a three-period, crossover design in which urea (u) was given at the rate of 20 g per kg dietary DM to half the animals. Twelve calves were allocated to the treatment sequences when they were approximately 12 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

1979
1979
1990
1990

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 8 publications
1
11
0
Order By: Relevance
“…The effects of additives containing HCHO or mixtures of formic acid and HCHO in reducing the products of fermentation have been recorded widely (Brown and Valentine, 1972;Wilkins et al, 1974;Wilkinson et al, 1976;Wilson and Wilkins, 1977), as have the effects of HCHO in reducing the digestibility of DM and organic matter (OM) (Grenet and Demarquilly, 1976;Barry, Cook and Wilkins, 1978). In general, depressions in fibre digestibility have been observed only at application rates of HCHO (in terms of g/kg CP) higher than those used in the present experiment (Wilkins, Wilson and Cook, 1975;Lonsdale, Thomas and Haines, 1977). When the primary growth silages used in the present trial were given to sheep as the sole feed, Siddons et al (1979) observed only a small depression in the proportion of cellulose digested in the rumen.…”
Section: Discussionmentioning
confidence: 53%
“…The effects of additives containing HCHO or mixtures of formic acid and HCHO in reducing the products of fermentation have been recorded widely (Brown and Valentine, 1972;Wilkins et al, 1974;Wilkinson et al, 1976;Wilson and Wilkins, 1977), as have the effects of HCHO in reducing the digestibility of DM and organic matter (OM) (Grenet and Demarquilly, 1976;Barry, Cook and Wilkins, 1978). In general, depressions in fibre digestibility have been observed only at application rates of HCHO (in terms of g/kg CP) higher than those used in the present experiment (Wilkins, Wilson and Cook, 1975;Lonsdale, Thomas and Haines, 1977). When the primary growth silages used in the present trial were given to sheep as the sole feed, Siddons et al (1979) observed only a small depression in the proportion of cellulose digested in the rumen.…”
Section: Discussionmentioning
confidence: 53%
“…However, intakes were similar for silages F and FF, and only when urea was added at the time of feeding (FFLU) was the voluntary intake of silage FF increased. Lonsdale et al (1977) recorded a significant increase of 25% when urea was added to silage treated with 7 or 14 g formaldehyde 100 g CP; and Tayler and Gibbs (1976) found non-significant increases in intake of up to 8% through the addition of urea to silage treated with 4-5 g formaldehyde 100 g CP. The levels of intake in early and mid lactation respectively of 1-5 and 2-2 kg/100 kg live weight as silage DM, and 2-8 kg/100 kg live weight as total DM in each lactation period are similar to values reported by Demarquilly and Dulphy (1976).…”
Section: Discussionmentioning
confidence: 99%
“…The response by calves given formaldehyde-treated silages is variable (Tayler and Wilkins, 1976) and the level of application of formaldehyde per unit of protein in the crop has been identified as a critical factor (Barry, 1976). In an experiment with calves the intake of silage treated with a relatively high level of formalin was lower than that of a formic acid-treated silage, but the addition of 2 % of urea to the silage dry matter (DM) at the time of feeding caused a significant increase in intake of the formalin-treated silage (Lonsdale, Thomas and Haines, 1977).…”
Section: Introductionmentioning
confidence: 99%
“…Lonsdale, Thomas and Haines (1977) observed that formaldehyde application at a rate similar to that used in the present trial (67 g formaldehyde per kg crude protein) reduced the voluntary intake of grass silage. In the present trial the depression in intake may in part be linked with a depression in digestibility.…”
Section: Discussionmentioning
confidence: 75%
“…In the present trial the depression in intake may in part be linked with a depression in digestibility. Lonsdale et al (1977) suggested that the low intake of silage preserved with high levels of formaldehyde could be associated with a lack of rumen-degradable N, although recent evidence from Kaiser (1979) indicates that the effect is complicated by the direct action of formaldehyde on digestion. In the present trial the reduced performance of calves given formaldehydepreserved silage as the sole feed was not present when the silages were supplemented with barley/fish meal but was again apparent when the silages were supplemented with dried grass.…”
Section: Discussionmentioning
confidence: 97%